2020
DOI: 10.1097/md.0000000000021463
|View full text |Cite
|
Sign up to set email alerts
|

Validating candidate biomarkers for different stages of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a common chronic condition caused by the accumulation of fat in the liver. NAFLD may range from simple steatosis to advanced cirrhosis, and affects more than 1 billion people around the world. To date, there has been no effective treatment for NAFLD. In this study, we evaluated the expression of 4 candidate NAFLD biomarkers to assess their possible applicability in the classification and treatment of the disease. Twenty-six obese subjects, who underwent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
(50 reference statements)
0
5
0
1
Order By: Relevance
“…In conclusion, the histological characteristics (significant fibrosis), enrichment analysis, and immune cell infiltration results (marked infiltration of M1 macrophages and CD8 T cells) all indicated that molecular subtype I was associated with significant fibrosis, and thus, molecular subtype I was named fibrotic NAFLD. Further, collagen type I alpha 1 chain (COL1A1) ( 14 ) and thrombospondin 2 (TSP2) ( 15 ) exhibited the highest expression levels in molecular subtype I as biomarkers of the advanced fibrosis stage of NAFLD ( Figures 8A, B ) , demonstrating that molecular subtype I had the most significant fibrosis. The treatment of molecular subtype I NAFLD should focus on decreasing liver collagen deposition and increasing fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the histological characteristics (significant fibrosis), enrichment analysis, and immune cell infiltration results (marked infiltration of M1 macrophages and CD8 T cells) all indicated that molecular subtype I was associated with significant fibrosis, and thus, molecular subtype I was named fibrotic NAFLD. Further, collagen type I alpha 1 chain (COL1A1) ( 14 ) and thrombospondin 2 (TSP2) ( 15 ) exhibited the highest expression levels in molecular subtype I as biomarkers of the advanced fibrosis stage of NAFLD ( Figures 8A, B ) , demonstrating that molecular subtype I had the most significant fibrosis. The treatment of molecular subtype I NAFLD should focus on decreasing liver collagen deposition and increasing fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…type I alpha 1 chain (COL1A1)(14) and thrombospondin 2 (TSP2) (15) exhibited the highest expression levels in molecular subtype I as biomarkers of the advanced fibrosis stage of NAFLD (Figures8A, B), demonstrating that molecular subtype I had the most significant fibrosis. The treatment of molecular subtype I NAFLD should focus on decreasing liver collagen deposition and increasing fibrinolysis.…”
mentioning
confidence: 99%
“…Захисний ефект генотипу AA SNV rs4374383 пов'язаний з низькою експресією гена MerTK у печінці. Клінічно значущий фіброз (стадії F2-F4) спостерігається у 19 % хворих з генотипом AA порівняно з 30 % хворих з генотипами GG або GA SNV rs4374383 (ВР = 0,43; 95% ДІ: 0,21-0,88) гена MerTK [125][126][127][128].…”
Section: генетичні фактори що впливають на розвиток метаболічно асоці...unclassified
“…Thus, a topical issue on the agenda is the search for new biomarkers of NAFLD progression. A suggestion regarding biochemical markers, e.g., using the content of some proteins in plasma, namely, PNPLA3 and PPP1R3B as biomarkers of steatosis and COL1A1 as a potential marker of fibrosis in NAFLD [19], is useful. Studies have argued that single biomarkers are hardly diagnostic or predictive of disease stages because of their heterogeneity [20].…”
Section: Approaches For Assessing Nafld Progressionmentioning
confidence: 99%
“…A previous study demonstrated that the activation of an axis, m 6 A-catalytic enzyme methyltransferase-like 3 [(METTL3)/ REVIEW Genes & cells Vol. 19 (1) 2024 metastasis-associated lung adenocarcinoma transcript 1 (MALAT1; a lncRNA)/polypyrimidine tract-binding protein 1 (PTBP1; an RNA-binding protein)/ubiquitin-specific peptidase 8 (USP8; a deubiquitinating enzyme)/transforming growth factor β-activated kinase 1 (TAK1, a kinase)], may promote pyroptosis and M1 polarization of hepatic macrophages [120]. Neutrophils and macrophages may also release exosomes that subsequently modify liver function.…”
Section: Macrophagesmentioning
confidence: 99%